Pembatalan Perkawinan Karena Hubungan Mahram: dalam Perspektif Hukum Islam - Nurhadi (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam, 2015)
Every human being on the surface of the earth in general always wanted a happy and trying to keep it still be his happiness. Something that happiness will not be achieved easily without complying with all the rules that have been laid down by religion. One manifestation of the greatness of Allah SWT for the creation of man is the creation of man consists of men - men and women with a pair - the pair. So also the country took part in arranging a marriage that is poured into the rules of state laws. In this journal will be explained in more detail.